Republic of Kenya : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Kenya. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses the Republic of Kenya's Request for Disbursement Under the Rapid Credit Facility (RCF). The coronavirus disease 2019 pandemic is taking a serious toll on the Kenyan economy, significantly reducing growth, creating fiscal and external financing needs. It is important that the authorities resume their fiscal consolidation plans to reduce macroeconomic vulnerabilities once the crisis abates. The pandemic has impacted nearly all facets of the economy-particularly tourism, transport, and trade-and led to urgent balance of payments and fiscal financing needs. Emergency financing under the RCF will deliver liquidity support to help Kenya cover its balance of payments gap this year. It will provide much-needed resources for fiscal interventions to safeguard public health and support households and firms affected by the crisis. It will also catalyze necessary financing from other donors. The Central Bank of Kenya (CBK) has taken various measures to maintain enough liquidity in the financial sector. It should continue to stand ready to further support the economy and the financial sector's health, as necessary, while ensuring that policy decisions are data driven. The CBK should also continue to allow the exchange rate to act as a shock absorber.